The Effect of Oxytocin Massage and Breast Care on Breast Milk Production in Primiparous Breastfeeding Mothers on Days 3-7 at the Sahu Public Health Center, West Halmahera - Sunarti Yanto; Widia Shofa Ilmiah (NAJ Nursing Applied Journal, 2025)
Breast milk production in the early postpartum period is a crucial factor for successful breastfeeding, particularly among primiparous mothers who often experience lactation difficulties during days 3–7 after childbirth. Non-pharmacological interventions such as oxytocin massage and breast care are considered effective approaches to support milk production by enhancing hormonal release and breast stimulation.This study employed a quantitative quasi-experimental design with a one-group pretest–posttest approach. The study was conducted at the Sahu Public Health Center, West Halmahera, involving 20 primiparous breastfeeding mothers on days 3–7 postpartum selected through purposive sampling. Oxytocin massage and breast care were administered according to standardized procedures. Breast milk production was assessed before and after the intervention using observational indicators of milk flow. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in breast milk production after the intervention. The mean breast milk production score decreased from 1.95 before the intervention to 1.15 after the intervention, indicating smoother milk flow. Statistical analysis revealed a significant difference in breast milk production before and after oxytocin massage and breast care (Z = −3.358; p = 0.001). Oxytocin massage combined with breast care significantly improves breast milk production among primiparous breastfeeding mothers during days 3–7 postpartum. These non-pharmacological interventions are safe, practical, and effective, and are recommended to be integrated into routine postpartum care to support early lactation success.